2011
DOI: 10.1021/bm200043u
|View full text |Cite
|
Sign up to set email alerts
|

α-Amino Acid Containing Degradable Polymers as Functional Biomaterials: Rational Design, Synthetic Pathway, and Biomedical Applications

Abstract: Currently, biomedical engineering is rapidly expanding, especially in the areas of drug delivery, gene transfer, tissue engineering, and regenerative medicine. A prerequisite for further development is the design and synthesis of novel multifunctional biomaterials that are biocompatible and biologically active, are biodegradable with a controlled degradation rate, and have tunable mechanical properties. In the past decades, different types of α-amino acid-containing degradable polymers have been actively devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
161
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 121 publications
(235 reference statements)
0
161
0
Order By: Relevance
“…22 Generally, implants which are degradable in vivo with an appropriate degradation rate allow host tissue growth until healing is complete, while eliminating the need for a second operation to remove the implant. 11,23 In this study, the n-CDHA-MAC composites with 30 wt% and 40 wt% exhibited suitable degradation in phosphate-buffered solution over time, and the mechanical strength of the 30 wt% n-CDHA composite was higher than that of the 40 wt% specimen after soaking for 12 weeks. Therefore, it could be suggested that the composite with 30 wt% n-CDHA has the potential to provide enough mechanical strength to meet the fundamental requirements of a bone substitute.…”
Section: Mechanical Propertiesmentioning
confidence: 62%
See 1 more Smart Citation
“…22 Generally, implants which are degradable in vivo with an appropriate degradation rate allow host tissue growth until healing is complete, while eliminating the need for a second operation to remove the implant. 11,23 In this study, the n-CDHA-MAC composites with 30 wt% and 40 wt% exhibited suitable degradation in phosphate-buffered solution over time, and the mechanical strength of the 30 wt% n-CDHA composite was higher than that of the 40 wt% specimen after soaking for 12 weeks. Therefore, it could be suggested that the composite with 30 wt% n-CDHA has the potential to provide enough mechanical strength to meet the fundamental requirements of a bone substitute.…”
Section: Mechanical Propertiesmentioning
confidence: 62%
“…11 However, these polymers generally have poor thermal stability, and poor processing and mechanical properties, so have limited biomedical applications. ω-amino acid has a structure similar to that of a L-amino acid and its polymer, polyamide, which has excellent mechanical and processing properties, as well as good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of the DDS should occur over an extended period of time to provide the patient effective treatment. A new class of amino acid based poly(ester amide) (PEA) polymers have been developed that meet the requirements of an efficient and useful drug delivery system [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of amino-acids as components of the PEA polymers confers several advantages. Degradation in vivo is accomplished by enzymes normally present in tissues, degradation begins at the surface allowing controlled zero order degradation [21,22], drugs are released with a zero order kinetics and the incorporation of amino acid-based building blocks [20] provide one or more functional groups along the polymer chain allowing modification of the polymer to tailor its physical and chemical properties, bio-erosion and performance as drug releasing vehicles, e.g. [16].…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions to resolve this problem is the development of biodegradable polymers. Biodegradable polymers are degraded eventually by microorganisms in the natural environments into carbon dioxide and water [2][3][4][5], which is not evident in non-biodegradable ones. Biodegradation of synthetic polymers is an important property in their many applications such as drug delivery, gene transfer, tissue engineering, and regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%